Forecasting Fisheries Production in Indonesia - Wicaksono, Bayu Rhamadani; Sutandi, Tendi; Tembo, Sydney (Jurnal Ekonomi & Studi Pembangunan, 2020)
The abundance of water resources avails Indonesia an excellent advantage in terms of the development of the capture and aquaculture fisheries. In recent years, Indonesian fish production has shown an increasing trend. The capture and aquaculture fisheries reached 6.6 million and 16.0 million tonnes respectively in 2016. The growing trend was translated into an average contribution of 2.4 percent towards the national GDP in 2013-2017. However, the absence of forecasting methods and data on fisheries production's potential growth contributes to ineffective policy interventions that require optimum production. Therefore, this study's main objective is to find the most accurate forecasting method for Indonesia's fisheries production. This research utilized the quarterly data of Indonesian fisheries production in 2000-2018 obtained from the Ministry of Marine Affairs and Fisheries. A comparative analysis of the Double Exponential and Seasonal ARIMA (SARIMA) method was undertaken to arrive at the most accurate forecasting method. The study findings broadly revealed that Indonesia's fish production was on an increasing trend, with aquaculture fisheries' contribution outweighing the capture fisheries in recent years. Furthermore, the SARIMA method was found to be the most accurate forecasting method compared to the Double Exponential method. The findings are useful for the government and related stakeholders for enhancing fish productivity in Indonesia. In addition, SARIMA methods could be used to forecast the fish production in upcoming years for better policy, strategy, and decision-making in developing the fisheries sector in Indonesia.